Viver com deficiência mental em Portugal durante a pandemia da COVID-19 - Iolanda Beatriz Barbosa Marques (2022)
The many frailties of the population with mental disability - psychological, physical, functional, social, among others - lead to their frequent and almost complete dependence on various supports. These limitations have severe damage on the life quality of the individual with the condition and on the functionality of his/her household. This situation was aggravated during the pandemic caused by COVID-19 due to factors such as the shutdown of disability support institutions and the higher rates of mortality and infection of this population explained by the institutional attendance, comorbidities and the need for physical support that doesn't allow compliance of protective measures (United Nations [UN], 2020). Thus, this study aims to investigate the soil in which the pandemic settled - highly marked by particularities of mental disability - and the consequences of these two factors' interaction in the quality of life of the individual with the condition. In order to explore these experiences, 12 semi-structured interviews were conducted with individuals of high and recognized influence in the lives of people with mental disability - 6 employees of mental disability support institutions and 6 relatives of individuals who attend them. These interviews were transcribed and analyzed according to the Thematic Analysis method (Braun & Clarke, 2006). This is an inductive analysis oriented according to a realistic/essentialist framework of the reported experiences. The participants consistently mentioned the relevance of institutional action on the lives of the mentally disabled population, such as the development of strategies and work adapted to their characteristics. The influences on the self-concept of this population, the impact of the household factors and the urgency of release from repressions directed to people with mental disability (that should be replaced by inclusion) were also explored. The pandemic has accentuated the fragilities of this population, marking it and its support agents through fear and uncertainty; however, the availability of institutional resources, resilience and community unity proved to be likely to promote a positive attitude during the pandemic.